Structure of Al-targets Used for PVD Coating in Jewellery - Kejzlar, Pavel; Andrsova, Zuzana; Švec, Martin (Manufacturing Technology Journal, 2015)
Aluminium, chromium, silver and other metal targets are often used for glass crystal coating in jewellery. The structure of targets strongly influences the quality of coating which leads to differences in their optical properties. The targets from two manufacturers were examined using scanning electron microscopy combined with EBSD with a goal to identify possible metallographic cause of defects arising on glass jewels.
Keywords: Aluminium; Structure; PVD; Thin layers; EBSD